2022
DOI: 10.1007/s10461-022-03899-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV Testing Among People Who Inject Drugs: Findings from a Multistate Study at the Start of the COVID-19 Pandemic

Abstract: stigmatization of substance use may also deter help-seeking behaviors among PWID [8][9][10].Throughout the world, the COVID-19 pandemic affected every aspect of public health, including the delivery of HIV prevention services [11][12][13][14]. For example, lockdowns and social distancing practices increased risk for IDU-associated HIV transmission due to reductions in SSP utilization, sterile syringe coverage, and HIV testing [14][15][16][17][18]. Many SSPs were also short-staffed during the COVID-19 pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These findings are consistent with other studies that found that lockdowns and social distancing practices reduced HIV testing and syringe services programmes in USA. 25 , 26 As regard MSM, a reduced access to HIV services together with continuation of HIV-risk behaviours was reported by a cohort study conducted among MSM in Italy. 27 Furthermore, recent studies highlight the COVID-19 impact in decreasing access to the community-based services testing among MSM in the WHO European region, as well as at a population level.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are consistent with other studies that found that lockdowns and social distancing practices reduced HIV testing and syringe services programmes in USA. 25 , 26 As regard MSM, a reduced access to HIV services together with continuation of HIV-risk behaviours was reported by a cohort study conducted among MSM in Italy. 27 Furthermore, recent studies highlight the COVID-19 impact in decreasing access to the community-based services testing among MSM in the WHO European region, as well as at a population level.…”
Section: Discussionmentioning
confidence: 98%
“…To overcome barriers and maintain access to HIV testing during times of crisis, such as global pandemics like COVID-19, healthcare systems and clinicians, have to consider expanding HIV programs, including HIV self-testing kits, telehealth, mobile HIV testing sites, and routine opt-out screening within health care settings (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used multivariate logistic regression to assess the difference in likelihood of HIV testing in lifetime (tested within past 12 months or tested but not within past 12 months vs. never tested) and HIV testing within past 12 months (vs. tested but not within past 12 months or never tested) between those with high versus low risk of HIV infection. In multivariate analyses, we adjusted for age, completion of high school versus less than high school or no answer, being unemployed versus unemployed or no answer, and monthly personal income above poverty line of 3,000 THB versus below poverty line or no answer, based on known predictors of HIV testing identified a priori in the literatures (Allen et al, 2023; Centre for SDG Research and Support, 2021). In the covariates, we decided to group together missing responses with the reference group in order to maximize statistical power, based on the assumption that those who refused to answer all had the same characteristics as those in the response group.…”
Section: Methodsmentioning
confidence: 99%